Onestop Solution Healthcare Distribution Service Perusahaan Pedagang Besar Farmasi (PBF) Distributor Healthcare PT Jagat Pharma Abadi - Patra Batam Prima; Deni Erlangga; Hasby Aprilian; Andri Subyakto (Syntax Corporation Indonesia, 2024)
The healthcare industry in Indonesia is experiencing rapid growth, which has triggered an increase in the need for efficient and effective health product distribution services. Pharmaceutical Wholesaler Companies (PBF) such as PT. Jagat Pharma Abbadi plays an important role in distributing health products from manufacturers to pharmacies and drug stores. This study aims to analyze the strategic planning of